Energy system contributions in middle-distance running events - Hill, D. W. (Journal of Sports Sciences, 1999)
The aim of this study was to estimate the energy contributions in middle-distance running events for male and female university athletes. The oxygen uptake (VO2) response during high-speed running was measured directly during exhaustive treadmill tests. Muscle mass was estimated using anthropometry. Each athlete completed an average of three races over 400 m, 800 m or 1500 m. Five minutes after each race, they provided a blood sample for determination of blood lactate concentration. For each race, energy cost, which was expressed as oxygen equivalents, was calculated as the sum of the aerobic and anaerobic components. The aerobic contribution was calculated as the sum of oxygen stores (2.3 ml O2.kg body mass-1) and total VO2 (based on the VO2 response to treadmill running). The anaerobic contribution was calculated as the sum of the energy available from phosphocreatine stores (37 ml O2.kg muscle mass-1) and the energy from glycolysis (3.0 ml O2.kg body mass-1 per mmol.l-1 increase in blood lactate concentration). For the women, the anaerobic energy contributions for the 400 m, 800 m and 1500 m averaged 62%, 33% and 17%, respectively. For the men, the anaerobic contributions averaged 63%,39% and 20%,respectively. This information will help coaches and sport scientists to design and implement individualized training programmes.